Cancer Immunotherapy: Platelet Membrane‐Camouflaged Magnetic Nanoparticles for Ferroptosis‐Enhanced Cancer Immunotherapy (Small 22/2020). Issue 22 (4th June 2020) - Jiang, Qin; Wang, Kuang; Zhang, Xingyu; Ouyang, Boshu; Liu, Haixia; Pang, Zhiqing; Yang, Wuli
Abstract : Malignant tumors pose a heavy threat to human health. In article number 2001704, Zhiqing Pang, Wuli Yang, and co‐workers present a multifunctional nanoplatform integrating platelet membrane with dual ferroptosis inducers for high‐performance ferroptosis‐enhanced immunotherapy of tumors. The biomimetic nanoparticles can not only make tumor ablation by ferroptosis, but also further awaken and boost immune cells to join forces to fight tumors.